(untitled) (Journal of Uzbekistan’s Development and Research, 2025)
This thesis is dedicated to exploring the management of marketing strategies in commercial banks to expand their customer base. It analyzes modern approaches to bank marketing, focusing on digital transformation, innovative services, and international best practices. The current state of Uzbekistan’s banking system is compared with global practices, and scientifically grounded conclusions are provided for developing effective marketing strategies. The study emphasizes the importance of contemporary tools such as customer experience (CX), customer relationship management (CRM) systems, artificial intelligence (AI), and big data analytics. The proposed strategies for Uzbekistan’s banks are tailored to local market characteristics while aligning with global standards.